Transformasi dalam novel ratu-ratu patani karya isma ae mohamad: kajian intertekstual julia kristeva - Islahuddin Islahuddin; Ku-Ares Tawandorloh; Romlee Hama; Fathiyah Chapakia (Universitas Ahmad Dahlan, 2020)
This study is aimed to describe the texts that discussing about transformation in the Ratu-ratu Patani by using the intertextual Julia Kristeva approach. The data of the study are texts of the Ratu-ratu Patani. The data are collected through reading and noting. They are analyzed by using the qualitative descriptive technique with a reference to theory and method of intertextual Julia Kristeva. The results of the research shows that transformations in Ratu-ratu Patani are ;1) The first female king; 2) conflict in the palace; 3) construction of Sungai Tambangan; 4) The return of the Ratu Ungu; 5) addressing the title ofÂ Paduka Syah Alam; 6) conflict outside the palace; 7) The visiting of Yang Dipertuan Muda Johor; 8) Siamese attacks Patani; 9) collection of assets; 10) The betrayal of the Yang Dipertuan Muda Johor against the Ratu Kuning. In addition, the results of the study indicates that the transformations found inÂ the novel Ratu-ratu Patani in accordance with the texts contained in the Hikayat Patani establishing before the novel Ratu-ratu Patani is written.